Does garlic oil have a role in the tratment of Helicobacter pylori infection - Ahmet AYDIN,; Galip ERSÖZ,; Oktay TEKEŞİN,; Eren AKÇİÇEK,; Müge TUNÇYÜREK,; Yücel BATUR, (Turkish Journal of Gastroenterology, 2019)
-